Tradisi Ruwahan pada Masyarakat Melayu Palembang dalam Perspektif Psikologi - Dwinanda, Poppy; Rahmawati, Richa Dwi; Fitriyani, Eka (Lembaga penelitian dan pengabdian kepada Masyarakat, 2022)
This paper aims to provide information about the Ruwahan tradition carried out by the Palembang Malay community and discuss it from a psychological perspective. The author obtains information from various relevant writing sources through the library research method. From the perspective of Psychology, the Ruwahan tradition of the Palembang Malay community, there is a social learning process, because this tradition is a learning process that is carried out from generation to generation. In the Ruwahan tradition, social interaction takes place in the form of cooperation, where the Palembang Malay people work together from the preparation stage until the Ruwahan tradition is completed. A Ruwahan tradition is a form of prosocial behavior, where the host invites neighbors and relatives to give charity without expecting anything in return.